DEEP-LEVEL KINETICS AND THERMOMECHANICAL WAVE PHENOMENA IN COMPENSATED SILICON UNDER PULSED HYDROSTATIC PRESSURE - R.Khamidov; A.Suvanov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This work investigates the fundamental mechanisms governing the transient piezoresistive response of nickel-compensated silicon (n-Si:P,Ni and p-Si:P,Ni) under pulsed hydrostatic pressure. The primary goal is to separate and analyze the static deformational, thermal, and kinetic-relaxation components of the conductivity change observed during and after a rapid pressure pulse. We combine a developed theoretical model of thermomechanical wave processes in the pressure-transmitting fluid with experimental measurements of current kinetics. The theoretical analysis demonstrates that high loading rates generate a non-stationary thermal field, leading to wave-like heat propagation. Experimentally, we observe a pronounced relaxation transient in compensated samples: after the pressure reaches its maximum amplitude of 0.5 GPa, the current continues to increase for several seconds, peaks, and then slowly decays to a steady-state value. A key finding is that the amplitude of this transient significantly exceeds the response caused by pure, isobaric heating of the sample to the same temperature, proving the existence of a pressure-specific, non-equilibrium ionization mechanism beyond simple adiabatic heating. Furthermore, the relaxation magnitude strongly depends on the compensation degree and is more prominent in n-type samples than in p-type ones, indicating the role of carrier type and lattice coupling. The main conclusion is that the dynamic tensoeffect in semiconductors with deep levels is a complex superposition of an instantaneous pressure-induced shift of electronic levels, a transient thermodeformational excitation, and a slow relaxation governed by the kinetics of deep-level occupancy